Pengaruh Kualitas Pelayanan Terhadap Loyalitas Nasabah pada LPD Desa Adat Anggungan, Lukluk, Mengwi, Badung, Bali - Primantari, Lekzy; Supriliyani, Ni Wayan; Yudartha, Putu Dharmanu (CITIZEN CHARTER, 2019)
ABSTRACT The existence of LPD in Bali plays a major role in constructing Desa Adat (village).To maintain the existence of LPD in Bali, the villagers need to support it and the staff also has to improve their service quality because the service quality can affect the customers’ loyalty. This study is to investigate the effect of service quality towards customers’ loyalty of LPD Desa Adat Anggungan. This study is a quantitative study which uses questionnaire technique to collect data. The sample of this study was 98 customers which is gathered by using Slovin pattern.To investigate the effect of independent variable towards dependent variable, the researcher did a simple linear analysis. Hypothesis testing was done using t test. The result of the study shows that the service quality gives positive and significant impact towards customers’ loyalty of LPD Desa Adat Anggungan. Keywords: Service Quality, Customers’ Loyalty, LPD ( Lembaga Perkreditan Desa)